2012
DOI: 10.1016/j.dsr2.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of Black Sea's hydrodynamics and connection to atmospheric patterns

Abstract: The long term variability of the Black Sea physical processes (e.g. temperature, main circulation, cold intermediate layer, sea level) and its relation to atmospheric conditions and large scale climate patterns are investigated using an eddy-resolving tridimensional model in combination with statistical tools (e.g Empirical Orthogonal Functions, Self Organizing Maps). First, the ability of the model to represent the interannual dynamics of the system is assessed by comparing the modeled and satellite sea surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 42 publications
1
36
0
2
Order By: Relevance
“…Temperature plays a critical role because of the special climatic feature of the Black Sea, where an exceptionally large zonal west-east temperature gradient exists with fall-winter temperatures in the southeastern region being ∼4-5 • C higher than the northwestern region (Buongiorno Nardelli et al, 2010;Capet et al, 2012). Anchovy can swim at high speeds of up to five body-lengths/s (bl/s) for long periods of time, as observed in Peruvian anchovy (Peraltilla and Bertrand, 2014), and similar swimming speeds have also been observed in the Black Sea anchovy (A.C. Gucu, pers.…”
Section: Parameterization Of Anchovy Behaviormentioning
confidence: 99%
“…Temperature plays a critical role because of the special climatic feature of the Black Sea, where an exceptionally large zonal west-east temperature gradient exists with fall-winter temperatures in the southeastern region being ∼4-5 • C higher than the northwestern region (Buongiorno Nardelli et al, 2010;Capet et al, 2012). Anchovy can swim at high speeds of up to five body-lengths/s (bl/s) for long periods of time, as observed in Peruvian anchovy (Peraltilla and Bertrand, 2014), and similar swimming speeds have also been observed in the Black Sea anchovy (A.C. Gucu, pers.…”
Section: Parameterization Of Anchovy Behaviormentioning
confidence: 99%
“…It resolves the currents and the physical state of the sea, which are temperature, salinity, internal mixing and surface elevation. The implementation used in the frame of these simulations is described in Capet et al (2012), and validated in detail with satellite sea surface temperature (SST) and sea level elevation data.…”
Section: The Coupled Modelmentioning
confidence: 99%
“…This indicates that climatic drivers mostly drive a shorter timescale variability while eutrophication drivers act on a longer term. Interestingly, the role of temperature introduces an oscillation in the interannual variations of hypoxia, which is related to the East Asia/West Russia atmospheric teleconnection pattern (Capet et al, 2012).…”
Section: Empiric Linear Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting cold intermediate layer (CIL) is a major feature of the Black Sea vertical structure. Cold intermediate water formation and advection by the cyclonic basin-wide Rim Current (Öszoy and Ünlüata, 1997;Capet et al, 2012) ventilate the oxycline and thereby influence variability in the depth of the upper suboxic interface . Recently, atmospheric warming (Oguz et al, 2006) was shown to reduce the ventilation of the lower oxic layer (Tugrul et al, 2014;Pakhomova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%